2005
DOI: 10.1111/j.1745-4522.2005.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

CONTENT OF TRANS C18:1 AND TRANS C18:2 ISOMERS AND CIS9TRANS11 C18:2 (CLA) IN FAT BLENDS

Abstract: The content of trans C18:1, trans C18:2 and cis9trans11 C18:2 (CLA) in the marketed fat blends was evaluated by capillary gas chromatography and silver thin-layer chromatography. For comparison, the level of these acids was also determined in commercial butter, purchased at the same time. The content of trans C18:1 in fat blends showed that half of the examined products contained trans C18:1 at 1.9-4.4%, while the other half contained 8.2-24.2% trans fatty acids. The fat blends with a high total content of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The products with a low level of trans 18:1 contained CLA at 0.3-1.0%. The content of CLA in fat blends with high levels of trans 18:1 did not exceed 0.3% [56]. Analysis of the fatty acid composition in French butters indicated that the average CLA content was 0.45 g/100 g butter in winter, 0.58 in spring and 0.80 in summer [57].…”
Section: An Important Source Of Cla -Dairy Productsmentioning
confidence: 90%
“…The products with a low level of trans 18:1 contained CLA at 0.3-1.0%. The content of CLA in fat blends with high levels of trans 18:1 did not exceed 0.3% [56]. Analysis of the fatty acid composition in French butters indicated that the average CLA content was 0.45 g/100 g butter in winter, 0.58 in spring and 0.80 in summer [57].…”
Section: An Important Source Of Cla -Dairy Productsmentioning
confidence: 90%
“…The level of CLA in milk fat mainly depends on the feeding period, as well as lactation period, breed and individual determinants of cows. According to literature data (Kelsey et al, 2003;Żegarska et al, 2006;Zunong et al, 2008;Frelich et al, 2012;Hanuš et al, 2016) higher contents of this fatty acid occur in fat of milk from the summer season and lower contents in milk fat from the winter season. The content of CLA in dairy products (fermented milk or cheeses) may differ from that in milk.…”
Section: Introductionmentioning
confidence: 97%